The value of the Committee on Agriculture: Mapping Q&As to trade flows - Lee Ann Jackson; Federica Maggi; Roberta Piermartini; Stela Rubínová (World Trade Organization (WTO), 2020)
What is the value of the WTO Committee on Agriculture? How much trade do countries talk about at the WTO? Do low-income countries participate less than they should in the work of the Committee? How important are issues not covered by notifications? What are the most important issues on which to focus negotiations? In this paper, we attempt to answer these questions building and analysing a new database. WTO regular bodies and the Secretariat collect information on measures notified and concerns raised by members on these measures in text format. We transform the qualitative database maintained through the AG-IMS into a quantitative one. We first introduce a new methodology to associate each question to a product and to its HS 4-digit code. Then, we attempt to match each of the 5'526 questions asked between 1996 and 2016 to the bilateral flows of the corresponding questioner and respondent at the HS 4-digit level. Our working dataset relies on the 3'295 questions that we are able to match. Using this new database, we show that (i) questions covered at least 778 billion of agricultural trade over the period 1996-2016 (or 3% of total trade in agriculture); (ii) on average, when a Member receives a question the questioners account for 48 per cent of its trade in the main product concerned; (iii) for each Member/product the share of trade discussed in the Committee is correlated with its share of global trade in agriculture; (iv) questions related to subsidies and to non-notified measures cover an increasing amount of trade.
Keywords: F13; F53; Q17; Q18; 330; Agricultural trade policies; Trade policy monitoring; WTO Transparency; WTOReforms; value of WTO; WTO as discussion forum